Effects of mitral annular calcification on the outcomes of transcatheter aortic valve implantation. (14th October 2021) - Sener, Y Z; Tokgozoglu, S L; Ardali, S; Karakulak, U N; Ates, A H; Sahiner, M L; Kaya, E B; Atalar, E; Ozer, N; Hazirolan, T; Aytemir, K
Abstract: Background: Transcatheter aortic valve implantation (TAVI) has become the standard of care treatment in patients with severe aortic stenosis who carry intermediate or high risk for surgical aortic valve replacement. Mitral annular calcification (MAC) is frequently seen in patients with aortic stenosis and it is associated with increased cardiovascular morbidity and mortality. It is reported that MAC is an independent predictor of all cause mortality after TAVI. Aim: The aim of this study is to both evaluate the relationship between mitral annular calcification and TAVI related complications and mortality; and to define the predictors of both all cause mortality and permanent pacemaker implantation after TAVI. Methods: All of the patients who underwent TAVI procedure due to severe aortic stenosis between 01.01.2020 and 01.06.2020 in our University Hospital were screened and patients fullfilling including criterias were enrolled. Patients' baseline demographic datas, laboratory, echocardiography and TAVI procedure related parameters were recorded. Outcomes are identified as follows; association between mitral annular calcification and TAVI related complications, establishment of the predictors of all cause mortality and permanent pacemaker implantation, definition of the in-hospital and all cause mortality rates. Results: A total of 245 patients including 98 males (40%) and 147 females (60%) were enrolled in the study. The mean age of the population was 76, 3±8, 3 years. The mean left ventricular ejection fraction was % 54, 8±11, 4; aortic valve area was 0, 74±0, 14 cm 2 and mean aortic transvalvular gradient was 47, 0±14, 3 mmHg. MAC was detected in 148 (% 60, 4) patients (Table 1). In-hospital mortality was occurred in 14 (5, 7%) cases. Permanent pacemaker implantation was performed in %17, 8 (n=42) patients and all cause mortality was developed in 89 (36, 3%) cases during the median 23, 1 (11, 6–44, 3) months follow-up. Pericardial effusion (26, 4% vs 12, 4%; p=0, 013) and contrast induced nephropathy (21, 6% vs 7, 2%; p=0, 005) were developed more frequently in patients with MAC than without MAC (Table-2). Only the presence of MAC extending to left ventricular outflow tract was detected to be independent predictor of permanent pacemaker implantation requirement (HR: 3, 32; p=0, 002). All cause mortality predictors were established as; use of renin-angiotensin-aldosterone system blockers (HR: p=0, 012), level of hemoglobin (HR: 0, 79; p=0, 006), severe mitral annular calcification (HR: 1, 94; p=0, 024) and atrial fibrillation development after TAVI (HR: 2, 39; p=0, 002). There was not any correlation between aortic valve area and MAC vloume (r=0, 03; p=0, 689), MAC Hounsfield Unit (r=−0, 007; p=0, 934) and MAC Agatston score (r=−0, 08; p=0, 290). Discussion: MAC is associated with all cause mortality after TAVI and MAC extending to left ventricular outflow tract is an independent predictor of permanent pacemaker implantation requirement. FUNDunding Acknowledgement: Type of funding sources: None.